PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR Go Public (Studi Empiris pada Perusahaan yang Terdaftar di BEI 2011 Sampai 2013) - Andri veno (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2015)
The purpose of this research was to examine the effect of Effect of Good Corporate Governance, which includes: the size of the directors council, commissioner council, the total of commissioner council, and the audit committee of the company's performance. This research used a sample of 48 companies listed on the stock exchanges of Indonesia, by using purposive sampling which publishes financial report for 3 years from 2011-2013. The method analysis of this research using multiple regression.Results from this research show that (1) The size of the council of directors significant positive effect to the corporate performance , (2) Independent council commissioner wasn’t significant effect to corporate performance (3) the total of council commissioner wasn’t significant effect to corporate performance (4) Audit Committee significant positive effect to corporate performance (5) Simultan, Size of the directors council, Independent of the commissioners council, the total of commissioners council and the Audit Committee had a significant effect to the corporate performance.